1991
DOI: 10.1093/bja/66.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of General Anaesthesia on the Pharynx

Abstract: Conventional lateral radiography was used in 18 elderly male patients to investigate the changes induced by general anaesthesia in the upper airway. The effect of tongue traction under anaesthesia was studied similarly in another 11 patients. Following induction of anaesthesia, there were highly significant approximations to the posterior pharyngeal wall of the soft palate (median change 1.3 mm, 95% confidence interval (Cl) 0.3-2.6 mm; P = 0.006), tongue base (mean change 6.5 mm, 95% Cl 5.3-7.7 mm; P less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(96 citation statements)
references
References 17 publications
1
90
0
5
Order By: Relevance
“…Head and neck movements change the shape of the pharynx, 18 and this can displace the SLA device 19 ; the SLIPA is not recommended when changing the head Values are expressed as mean ± standard deviation or absolute number * Number of patients in SLIPA group is 50 because one failed insertion is included in the analysis. P \ 0.05 between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck movements change the shape of the pharynx, 18 and this can displace the SLA device 19 ; the SLIPA is not recommended when changing the head Values are expressed as mean ± standard deviation or absolute number * Number of patients in SLIPA group is 50 because one failed insertion is included in the analysis. P \ 0.05 between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Insertion of an oral airway during light anaesthesia is therefore contraindicated. Recent radiographic and MRI studies have shown that, at induction of anaesthesia, the most important cause of obstruction is not, as previously thought, posterior displacement of the tongue, but approximation of the soft palate to the posterior pharyngeal wall [4,5]. We have found that the use of a nasal airway, rather than an oral airway, helps to smooth out this difficult, initial phase of induction.…”
Section: Upper Airway Obstructionmentioning
confidence: 60%
“…Because a standard mask does not fit easily onto the cheeks of edentulous patients, face mask ventilation may be hard to perform (18). The airway may also be obstructed by movement of the tongue, soft palate, and epiglottis to the rear, whereas the space for air is lessened in the oropharynx due to low muscle tone caused by general anesthesia (19). In edentulous geriatric patients, sunken cheeks may make ventilation with a mask ineffective and perhaps even impossible (20).…”
Section: Discussionmentioning
confidence: 99%